ПРОБЛЕМА ПРОДУКТИВНОСТІ ЛІСОВИХ НАСАДЖЕНЬ КОЛИШНІХ КОЛЕКТИВНИХ СІЛЬСЬКОГОСПОДАРСЬКИХ ПІДПРИЄМСТВ ЗАКАРПАТСЬКОЇ ОБЛАСТІ - Kichura, V. P.; Kichura, A. V. (Forestry and Forest Melioration, 2018)
Introduction Questions of productivity of forests are important for forestry science and practice. The productivity of tree stands serves as an integrated measure to assess the level of forest management. In the same forest site conditions, the level of managing would be higher in forest areas with high productivity of stands. Forests of former collective agricultural enterprises in the Transcarpathian region were selected as the object of our study, which were transferred to the jurisdiction of the State Forest Resources Agency of Ukraine from the Ministry of Agrarian Policy and Food in 2016. The aim of the research was in attempt to determine the productivity of the transferred forests and to provide the assessment of the level of managing them on this basis. The most important objective of the research was to establish and analyse the problems of forest management in transferred forests to avoid such shortcomings in the future. Materials and Methods The productivity of forest areas and forest fund in generally was studied in a systemic way with using tested in forestry and forest inventory methods. For the study, the data from the State Forest Cadastre (2011), accounting and project indicators of production association “Ukrderzhlisproekt” and data of manufacturing and statistical reports of forestry companies in the region were used. Results and Conclusions Forests, which were managed by former collective and state farms in the Transcarpathian region, occupied an area of over 136 thousand hectares. As a result of a long reform, today these forests are transferred from the sphere of management of the Ministry of Agrarian Policy and Food to the State Forest Resources Agency of Ukraine. Most of these forests (about 100 thousand ha), which have been transferred recently, have low productivity. In Transcarpathian region, forests of Ministry of Agrarian Policy had low productivity for many reasons over almost a half-century. The productivity in terms of total stock volume on 1 hectare of land covered with forest vegetation did not match the potential of forest conditions and was 1.5–2 times less than the productivity of forests subordinated to the State Forest Resources Agency. Low productivity of the studied forests has a systemic character, almost independent of the placement of these forests in the region and appears in forest stands of all regular users of Ministry of Agrarian Policy of Ukraine within households and age groups. The main reason for poor productivity of the investigated forests lies in the insufficient level of management of forestry production for nearly a half-century period. Problems of managing in forests of Ministry of Agrarian Policy, which have been transferred to the State Forest Resources Agency of Ukraine, require effective management solution in the short term by implementing a set of measures ranging from scientific justification, conducting of basic and continuous forest management and implementation projected forestry activities under increased supervision, aimed at improving the productivity of forest stands. 8 Tables, 7 Refs.